1990
DOI: 10.1128/jb.172.11.6469-6475.1990
|View full text |Cite
|
Sign up to set email alerts
|

Enterohemolysin production is associated with a temperate bacteriophage in Escherichia coli serogroup O26 strains

Abstract: A temperate bacteriophage that determines the expression of enterohemolysin was isolated from Escherichia coli 026 strain C3888. The genetic determinant associated with enterohemolysin production (E-Hly determinant) was cloned from EcoRI-digested bacteriophage DNA in vector plasmid pUC8. pUC8 recombinant plasmid pEOl9 carries a 3.7-kb EcoRI insert of phage DNA, and enterohemolysin was expressed in E. coli K-12 after transformation. Hemolysin-negative derivatives of pEOl9 were generated by transposon mutagenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…2). This observation differs from previous reports, which describe the lack of haemolytic activity in the culture supernatant of strain C3888 (Beutin et al 1990, Figueiredo et al 2003. However, these authors detected such activity in disrupted bacterial cells collected by centrifugation.…”
Section: Resultscontrasting
confidence: 99%
“…2). This observation differs from previous reports, which describe the lack of haemolytic activity in the culture supernatant of strain C3888 (Beutin et al 1990, Figueiredo et al 2003. However, these authors detected such activity in disrupted bacterial cells collected by centrifugation.…”
Section: Resultscontrasting
confidence: 99%
“…The bacteriophage-associated enterohemolysin (e-hlyA) is genetically unrelated to the plasmid-carried ehxA (38)(39)(40). It was suggested that the e-hlyA determinant does not encode a hemolysin, per se, as reported in earlier studies (38,39), but instead causes the release of the silent hemolysin by lysis of the bacterial cells (40).…”
mentioning
confidence: 60%
“…It was suggested that the e-hlyA determinant does not encode a hemolysin, per se, as reported in earlier studies (38,39), but instead causes the release of the silent hemolysin by lysis of the bacterial cells (40). The silent hemolysin (sheA), also called cytolysin A, encodes a pore-forming toxin (41,42) not related to the RTX family (43,44).…”
mentioning
confidence: 91%
“…The gene structure of this hemolysin is still unknown. A 60-kDa outer membrane protein, present only in EHly-positive bacteria (5), may be the EHly itself, but no further information on the purification of this protein is available. In the present paper, we describe the purification of EHly and show that it shares several properties with thiolactivated hemolysins having the following general characteristics, in addition to being inactivated by cholesterol: inactivation by oxidation and reactivation with reducing agents, lethality to mice, and lytic activity towards eukaryotic cells through the formation of pores in the cell membrane (6).…”
mentioning
confidence: 99%